D-Cysteine Ethyl Ester Reverses the Deleterious Effects of Morphine on Breathing and Arterial Blood–Gas Chemistry in Freely-Moving Rats - Getsy, Paulina M.; Baby, Santhosh M.; May, Walter J.; Young, Alex P.; Gaston, Benjamin; Hodges, Matthew R.; Forster, Hubert V.; Bates, James N.; Wilson, Christopher G.; Lewis, Tristan H. J.; Hsieh, Yee-Hee; Lewis, Stephen J. (Frontiers in Pharmacology, 2022)
Cell-penetrant thiol esters, including the disulfides, D-cystine diethyl ester and D-cystine dimethyl ester, and the monosulfide, L-glutathione ethyl ester, prevent and/or reverse the deleterious effects of opioids, such as morphine and fentanyl, on breathing and gas exchange within the lungs of unanesthetized/unrestrained rats without diminishing the antinociceptive or sedative effects of the opioids. We describe here the effects of the monosulfide thiol ester, D-cysteine ethyl ester (D-CYSee), on intravenous morphine-induced changes in ventilatory parameters, arterial-blood gas chemistry, Alveolar-arterial (A-a) gradient (i.e., index of gas-exchange in the lungs) and sedation and antinociception in freely-moving rats. The bolus injection of morphine (10 mg/kg, IV) elicited deleterious effects on breathing, including depression of tidal volume, minute ventilation, peak inspiratory flow, and inspiratory drive. Subsequent injections of D-CYSee (2 x 500 umol/kg, IV, given 15 min apart) elicited an immediate and sustained reversal of these effects of morphine. Morphine (10 mg/kg, IV) also elevated A-a gradient (mismatch in ventilation-perfusion within the lungs) and elicited pronounced changes in arterial blood-gas chemistry, including pronounced decreases in arterial blood pH, pO2 and sO2 an equally pronounced increases in pCO2 (all responses indicative of decreased ventilatory drive). These deleterious effects of morphine were immediately reversed by injection of a single dose of D-CYSee (500 umol/kg, IV). Importantly, the sedation and antinociception elicited by morphine (10 mg/kg, IV) were minimally affected by D-CYSee (500 mol/kg, IV). In contrast, none of the effects of morphine were affected by administration of the parent thiol, D-cysteine (1 or 2 doses of 500 umol/kg, IV). Taken together, these data suggest that D-CYSee may exert its beneficial effects via entry into cells that mediate the deleterious effects of opioids on breathing and gas-exchange. Whether D-CYSee is acting as a respiratory stimulant or by counteracting the inhibitory actions of µ-opioid receptor activation remains to be determined. In conclusion, D-CYSee and related thiol esters may have clinical potential for the reversal of the adverse effects of opioids on breathing and gas-exchange, while largely sparing antinociception and sedation.